Effectiveness of Sulfuryl Fluoride Fumigation for the Control of Phosphine-Resistant Grain Insects Infesting Stored Wheat. Issue 2 (7th January 2016) - Opit, George P.; Thoms, Ellen; Phillips, Thomas W.; Payton, Mark E.
Abstract : A field experiment was conducted in eight 13.6-MT steel bins containing 6.8 MT each of wheat to assess efficacy of sulfuryl fluoride or SF fumigant to control phosphine-resistant and susceptible Rhyzopertha dominica (F.) and Tribolium castaneum (Herbst). Approximately 400 adults of each type of beetle were added to each bin. Additionally, muslin bags containing immature stages and adults, with their respective diets, were also placed in bins. Four bins were fumigated with SF and others were untreated control bins. The SF dosages in treated bins ranged from 1, 196–1, 467 mg-h/liter. Mortality of adults in each bag was assessed 5 d postfumigation; diet minus adults was incubated in a jar, and number of adults counted after 8 wk. No significant change occurred in number of insect-damaged kernels in SF-treated bins. In trier samples from SF-treated bins, R. dominica numbers declined from 24 prefumigation to 0 at 3- and 6-wk postfumigation; T. castaneum numbers were unchanged. In WBII traps from SF-treated bins, numbers R. dominica and T. castaneum declined from 25 and 33, respectively, prefumigation to 0 or near 0 at 3- and 6-wk postfumigation. Mortalities of resistant and susceptible adult R. dominica, and adult and large larvae of T. castaneum in SF-treated bags was 100%. For all four types of beetles, adult numbers in jars associated with SF-treated bins were 0 or near 0. Results show SF is effective against all life stages of phosphine-resistant R. dominica and T. castaneum, and can be used for phosphine resistance management.